Tinjauan Literatur: Hubungan Penguasaan Teori Bilangan Cacah dengan Kemampuan Mengajar Guru SD - Nurhaswinda Nurhaswinda; Amalia Alfazira; Annisa Urrosada; Khusnul Putri Aprilliani; Nabilah Putriana; Regina Arifin; Vivi Maulia Cahyani.S; Sabrina Putri; Tatia Maharani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify and analyze recent findings related to elementary school teachers' mastery of whole number concepts and its impact on the quality of mathematics instruction. The method used is a literature review with a descriptive qualitative approach. Data sources were obtained from accredited national and international scientific articles published between 2008 and 2025. The focus of the review includes conceptual understanding of whole numbers, instructional strategies, the use of media and technology, and other pedagogical aspects. Data were collected by searching academic databases such as Google Scholar, ERIC, ScienceDirect, and Garuda using relevant keywords. Thematic analysis was conducted to identify key issues found in the literature. The findings indicate that teachers' conceptual mastery of whole numbers significantly influences their instructional strategies, use of technology, and ability to address students' misconceptions. Additionally, challenges such as limited training and learning resources were found to affect the effectiveness of mathematics instruction in elementary schools.